Records on indigenous antagonists of Phyllocnistis citrella Stainton (Lepidoptera Gracillariidae) new for ltaly (Bollettino di zoologia agraria e bachicoltura, 2024)
From December 1997 to March 1999 samples of leaves infested byCitrus Leaf Miner Phyllocnistis citrella (CLM)_Stainton were collected in severalcitrus groves around Palermo in arder to bred indigenous parasitoids. Among thedifferent species of Eulophid wasps emerged also: Asecodes delucchii (Boucek),Baryscapus sp., Elasmus sp., Aprostocetus sp.. This latter species was alsoobtained by Stigmella sp. on Ulmus sp .. In Italy these parasitoids were not knownto attack the already mentioned Gracillariid. Among those already known alldevelopmental stages of Semielacher petiolatus (Girault) were observed duringwinter 1998-1999. These records highlight a probable permanent establishmentof this parasitoid in the Sicilian citrus groves. With the aim of strengthening thenatural biological control against the CLM, a strain of Citrostichusphyllocnistoides (Narayanan) introduced from Jordan is now bred in arder tosupport its releases into citrus groves of the Island.
Keywords: Citrus Leaf Miner; antagonists; alternative host; Semielacher petiolatus establishment in Sicily